Developing a content subscale to assess university students' argumentative essays - Nimehchisalem, Vahid; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2013)
Genre-specific scales are available to evaluate students’ writing in English as a Second Language (ESL) situations, but instructors may still feel a need to develop new scales to match their specific testing situations. In order to develop a valid instrument for their testing situation, the researchers reviewed the literature and carried out a survey as well as a focus group study. These led them to a number of subscales, namely, content, organization, vocabulary, language conventions and overall effectiveness. The paper reviews how the band descriptors for the content subscale of the Analytic Scale of Argumentative Writing (ASAW) were determined. Toulmin’s (1958/2003) model was used to analyze the patterns of argument in 20 purposely selected argumentative essays written by a group of Malaysian students. The results of the analysis provided the researchers with descriptors for five levels of writing ability. The subscale was tested for inter- and intra-rater reliability as well as concurrent validity. Positive results were observed. ESL writing instructors and evaluators may find the subscales useful for formative assessment purposes. In addition, the samples can be useful models for ESL students to differentiate the successful from unsuccessful argumentative content in writing courses.